Pengembangan Model Bimbingan Perkembangan terhadap Kecerdasan Spiritual Anak Melalui Pendidikan yang Mencerahkan - Elfiah, Rifda (Universitas Islam Negeri Raden Intan Lampung, 2016)
Entering the third millennium, the development of intelligence in humans at least there has been a spectacular change. When the first term of intelligence as though only monopolized sense or reason (intellectual), but a series of the recent discovery in the field of modern psychology, legend IQ as the sole parameter intelligence fell. Currently, it is believed that the intelligence turned out to be complex (compound), which is referred to as Gardner's multiple intelligences. If during intelligence interpreted as if reason or logic, though now encroaching upon the emotional and spiritual. Goleman has popularized the emotional intelligence as breakthrough new ways to measure the extent of human intelligence in controlling emotions, bring a sense of empathy, understand the feelings of self and others, as well as how to control him. But people are still faced with the problem of